The influence of social movements on space astronomy policy: The cases of "Hubble Huggers", JWST's "Science Warriors" and the ISEE-3 "Reboot Team". (February 2015) - Harris, Hannah E.; Russo, Pedro
Abstract: Public engagement (PE) initiatives can lead to a long term public support of science. However most of the real impact of PE initiatives within the context of long-term science policy is not completely understood. An examination of the National Aeronautics and Space Administration's (NASA) and European Space Agency's (ESA) Hubble Space Telescope, James Webb Space Telescope, and NASA's International Sun/Earth Explorer 3 reveal how large grassroots movements led by citizen scientists and space aficionados can have profound effects on public policy. We explore the role and relevance of public grassroots movements in the policy of space astronomy initiatives, present some recent cases which illustrate policy decisions involving broader interest groups, and consider new avenues of PE including crowdfunding and crowdsourcing.